EMERGENCY PERI PARTUM HYSTERECTOMY-A LIFE SAVING PROCEDURE - Fawad, Anisa; Naz, Humaira; Nelofar, Talat; Abbasi, Aziz -un-Nisa (Journal of Ayub Medical College Abbottabad, 2015)
Background: Sub-total abdominal hysterectomy is a surgical procedure in which body of the uterus is removed while ovaries and cervix are preserved. The study was done with the objectives of assessing the frequency of peripartum hysterectomies, common indications and risk factors associated with this surgery. The postoperative complications including the severity of anaemia in these patients and need for blood transfusion and use of blood products like fresh frozen plasma and platelet concentrates were also studied. Methods: The study was based on the review of the records of Gynae ’˜A’ Unit, Ayub Teaching Hospital, Abbottabad from January 2011 till December 2012. Data was collected from the unit record and patient’s personal files. All the patients who underwent emergency peripartum hysterectomy were included in the study. Results: During this study period there were 6535 total deliveries in the unit, 2153 vaginal deliveries and 1786 caesarean sections. Emergency perpartum hysterectomy was needed in 72 patients. In the majority of the patients the gestational age was at term. The commonest indications for this operation was haemorrhage (placental abruption) 26 patients (36% ) followed by ruptured uterus in 18 patients (25%), prolonged and obstructed labour promoted uterine atony needing hysterectomy in 13 patients (18%). Placenta previa major degree needed hysterectomy in 9 patients (12.5%) while placenta increta and chorioamnionitis each accounted for 3 cases (4.2%). At admission the majority of the patients were severely anaemic 31 patients (43.05%). The most important risk factor identified was hypertensive disorders of pregnancy 26 patients (36%), followed by uterine atony in 13 patients (18.05%). Conclusion: High risk obstetric patients, prone to peripartum hysterectomy, should be identified by health personnel working in the rural areas and should be timely referred to the hospitals where appropriate facilities are available for the management of such patients. Keywords: Peripartum hysterectomy, Sub-total abdominal hysterectomy, placental abruption